Estimation of human capital in the strategic budgeting system - Kamenska, O.; Vesela, N. (Економічний вісник Донбасу, 2016)
This paper proposes a method for calculating assessment of employees working abilities in the system of strategic budgeting of an industrial enterprise, which is based on the synthesis of components of the qualification indexes of employees and which, in contrast to the existing ones, takes into account the relation between the strategic objectives and cost items in the budget of the enterprise. This method allows disclosure of the potential value of human capital and the compliance of its quality with strategic priorities of the company. У статті запропоновано метод розрахунку оцінки трудових можливостей робітника у системі стратегічного бюджетування промислового підприємства, який базується на основі синтезу складових кваліфікаційних ознак робітника підприємства та, на відміну від існуючих, враховує взаємозв’язок між стратегічними цілями та статтями витрат у бюджеті підприємства. Ццей метод дозволяє визначити потенційну цінність людського капіталу та відповідність його якості стратегічним пріоритетам підприємства. В статье предложен метод расчета оценки трудовых возможностей работника в системе стратегического бюджетирования промышленного предприятия, который базируется на основе синтеза составляющих квалификационных признаков работника предприятия и, в отличие от существующих, учитывает взаимосвязь между стратегическими целями и статьями затрат в бюджете предприятия. Этот метод позволяет определить потенциальную ценность человеческого капитала и соответствие его качества стратегическим приоритетам предприятия.